Direct Probing of Germinal Center Responses Reveals Immunological Features and Bottlenecks for Neutralizing Antibody Responses to HIV Env Trimer - Havenar-Daughton, Colin; Carnathan, Diane G.; Torrents de la Peña, Alba; Pauthner, Matthias; Briney, Bryan; Reiss, Samantha M.; Wood, Jennifer S.; Kaushik, Kirti; van Gils, Marit J.; Rosales, Sandy L.; van der Woude, Patricia; Locci, Michela; et al. (Cell reports (Cambridge), 2016)
Generating tier 2 HIV-neutralizing antibody (nAb) responses by immunization remains a challenging problem, and the immunological barriers to induction of such responses with Env immunogens remain unclear. Here, some rhesus monkeys developed autologous tier 2 nAbs upon HIV Env trimer immunization (SOSIP.v5.2) whereas others did not. This was not because HIV Env trimers were immunologically silent because all monkeys made similar ELISA-binding antibody responses; the key difference was nAb versus non-nAb responses. We explored the immunological barriers to HIV nAb responses by combining a suite of techniques, including longitudinal lymph node fine needle aspirates. Unexpectedly, nAb development best correlated with booster immunization GC B cell magnitude and Tfh characteristics of the Env-specific CD4 T cells. Notably, these factors distinguished between successful and unsuccessful antibody responses because GC B cell frequencies and stoichiometry to GC Tfh cells correlated with nAb development, but did not correlate with total Env Ab binding titers. [Display omitted] •Fine needle aspirates quantitatively monitor germinal center activity in lymph nodes•Neutralizing antibodies correlate with GC B cell magnitude, not ELISA Ab titers•Tfh cell quality is associated with vaccine-elicited HIV-neutralizing antibodies•LN FNA probing of GCs should be an immune correlate in HIV vaccine trials This study explores the immunological process by which a protein vaccine elicits HIV-neutralizing antibodies. Using direct probing of lymph nodes, Havenar-Daughton et al. show that neutralizing antibody development correlates with germinal center B cell frequencies and Tfh cells and that those responses can be tracked by LN FNAs over time.